If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11=-3(2y-2)-7
We move all terms to the left:
11-(-3(2y-2)-7)=0
We calculate terms in parentheses: -(-3(2y-2)-7), so:We get rid of parentheses
-3(2y-2)-7
We multiply parentheses
-6y+6-7
We add all the numbers together, and all the variables
-6y-1
Back to the equation:
-(-6y-1)
6y+1+11=0
We add all the numbers together, and all the variables
6y+12=0
We move all terms containing y to the left, all other terms to the right
6y=-12
y=-12/6
y=-2
| 41x-4x=13-8x | | 41x−4x=13−8x | | 10-2x=-6+6x | | 4x+11=-59−6x | | 0.4x-7=0.3x=2.8 | | 3x*4x=34 | | 5x2+16x-15=0 | | 2/3a+2=4/3+1/3 | | -6/7w=-36 | | x+21,7=40,4 | | -151=-10c+9 | | -s=71 | | z+22,7=38,4 | | 144-108+2x=180 | | 7(x-7)=-28x= | | y/13-2=6 | | 20x+3x-19x-3x+x=14 | | 50,000=2/3x+12 | | 68=12+8x | | w+4.5=8.11 | | 5(2x+25)=225 | | 4u-u+3u+3u-3u=18 | | 31=5x+9 | | 13=c/3-10 | | 8.6b+0.4=17 | | -12=3r+9r | | (6)/(5-5i)=3+3i/5+5 | | 7(x-7)=5x+4 | | 8b-8b+5b+3b=8 | | -34=f/4+-38 | | y=9.3 | | (7x+1/2)+(5x-81/2=) |